2010
DOI: 10.1007/s12311-010-0219-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Ethanol-Induced Death of Cerebellar Granule Cells

Abstract: Maternal ethanol exposure during pregnancy may cause fetal alcohol spectrum disorders (FASD). FASD is the leading cause of mental retardation. The most deleterious effect of fetal alcohol exposure is inducing neuroapoptosis in the developing brain. Ethanol-induced loss of neurons in the central nervous system (CNS) underlies many of the behavioral deficits observed in FASD. The cerebellum is one of the brain areas that is most susceptible to ethanol during development. Ethanol exposure causes a loss of both ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 116 publications
1
70
0
1
Order By: Relevance
“…These potential mechanisms include interference with neurotrophic factor-and retinoid acid-mediated signaling, induction of oxidative stress, DNA damage and ER stress, increased proinflammatory proteins, disruption of the neurotransmitter system, and inhibition of translational regulation. [28][29][30][31][32][33] As mentioned above, autophagy can be activated by various types of cellular stress including deprivation of nutrients, hypoxia, oxidative stress, ER stress, DNA damage, and protein aggregates, as well as by the presence of intracellular pathogens. 16,34 We have recently shown that ethanol activates autophagy in neurons in vitro and in the developing brain.…”
Section: Autophagic Protection Against Ethanol-mediated Neuronal Damagementioning
confidence: 99%
See 1 more Smart Citation
“…These potential mechanisms include interference with neurotrophic factor-and retinoid acid-mediated signaling, induction of oxidative stress, DNA damage and ER stress, increased proinflammatory proteins, disruption of the neurotransmitter system, and inhibition of translational regulation. [28][29][30][31][32][33] As mentioned above, autophagy can be activated by various types of cellular stress including deprivation of nutrients, hypoxia, oxidative stress, ER stress, DNA damage, and protein aggregates, as well as by the presence of intracellular pathogens. 16,34 We have recently shown that ethanol activates autophagy in neurons in vitro and in the developing brain.…”
Section: Autophagic Protection Against Ethanol-mediated Neuronal Damagementioning
confidence: 99%
“…ER stress can activate autophagy by disrupting intracellular Ca 2C homeostasis or activating kinases and transcription factors that regulate autophagy; these include ERN1, MAPK/JNK, DDIT4/REDD1, AKT, DDIT3/CHOP, XBP1, DAPK1, and NFE2L1/NFE2L2. 52,61,62 Since ethanol induces ER stress in cultured neurons and in the brain, 31,33 it may trigger autophagy by inducing ER stress in neurons.…”
Section: Er Stressmentioning
confidence: 99%
“…Neurotoxic effects of neonatal alcohol exposure on cellular death depend on brain region, neuronal population and treatment period [56][57][58]. Alcohol-induced neuronal death is mainly mediated by the mitochondrial apoptotic pathway also known as intrinsic apoptotic pathway [59,60].…”
Section: Alcohol Induces Apoptotic Cellular Deathmentioning
confidence: 99%
“…Alcohol-induced neuronal death is mainly mediated by the mitochondrial apoptotic pathway also known as intrinsic apoptotic pathway [59,60]. The Bcl-2 family proteins are critical factors triggering intrinsic apoptotic pathway [58]. Indeed, ethanol exposure up-regulates pro-apoptotic Bax and Bad, but down-regulates anti-apoptotic Bcl2 in neonatal rat brain [61,62].…”
Section: Alcohol Induces Apoptotic Cellular Deathmentioning
confidence: 99%
“…The Purkinje cells in a more advanced state of differentiation are more vulnerable to ethanol-induced cell death than those less matured [4]. It is known that the rat cerebellum is particularly sensitive to ethanol during the first period after birth [19], which is considered to be equivalent to the third trimester of human pre -…”
Section: Introductionmentioning
confidence: 99%